2015
DOI: 10.1111/ijmr.12059
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Rigor Trends in Retailing Research: Assessment and Guidelines

Abstract: This study presents an evaluation of research diversity and rigor levels in the retail marketing literature in order to glean valuable insights for researchers. Retailing is a significant sub‐field within marketing, and occupies a large portion of the extant marketing literature. The study consists of a content analysis of 600 quantitative empirical articles in the top six marketing journals (i.e. Journal of Retailing, Journal of Marketing, Journal of the Academy of Marketing Science, Journal of Consumer Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 85 publications
(202 reference statements)
0
17
0
Order By: Relevance
“…Hopefully, a comprehensive review may help identify what we know and what we should know about the EO within family firms. Additionally, literature reviews often highlight strengths and weaknesses within disciplines, provide examples of best practices to guide scholars in producing high-quality research, ratify the validity of findings, and deliver scientific evidence underpinning scholars’ advice to practitioners (Finnegan, Runyan, González-Padron, & Hyun, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hopefully, a comprehensive review may help identify what we know and what we should know about the EO within family firms. Additionally, literature reviews often highlight strengths and weaknesses within disciplines, provide examples of best practices to guide scholars in producing high-quality research, ratify the validity of findings, and deliver scientific evidence underpinning scholars’ advice to practitioners (Finnegan, Runyan, González-Padron, & Hyun, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They did so for instance by subjecting extracted data to specific additional qualitative or quantitative analyses (e.g. Cheng, 2016; Finnegan et al., 2016) or by using conceptual frameworks, derived a priori , to guide and organize their SR (e.g. Kokkonen & Alin, 2015; Wong et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Far from embracing the different perspectives offered by grey literature, some authors explicitly chose to exclude such sources (e.g. Finnegan et al., 2016; Keupp & Gassmann, 2009; Mariano & Awazu, 2016), usually arguing that academic papers provide a more suitable and high‐quality coverage of the subject under review. Frequently they cited Podsakoff et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rigor in academic research refers to "demonstrating a soundness regarding its theoretical and conceptual development, its methodological design and execution, its interpretation of findings, and its use of these findings in extending theory or developing new theory" (Zmud, 1996, p. xxxvii). Failure to preserve methodological rigor may lead to wrong empirical results and theoretical inferences, compromising our ability to develop knowledge and inform managers (Finnegan et al, 2016). In qualitative research, rigor can be demonstrated through transparency, which requires that researchers supply an audit trail outlining what they did, how they did it, and why they did it (including the researchers' reflexive position).…”
Section: Interest Rigor Relevance and Richnessmentioning
confidence: 99%